Seismic investigation and upgrading of disused industrial buildings a case study - Longobardi, Giovanna; Davino, Antonio; Formisano, Antonio (Technical Annals, 2023)
In this paper, the evaluation of the seismic behaviour and the consolidation plan of a former industrial building are described. After a short introduction regarding the value of industrial architecture, discovered only in the late ‘70s of the past century, and the necessity to intervene on this heritage, most of time abandoned, the case study has been introduced. It is a former tobacco industry placed in a small village in the outskirt of Salerno, in the South Italy. Firstly, the historical evolution of the property has been reconstructed. Then, the main structural and architectonical features of the building have been illustrated. After this knowledge phase, the seismic behaviour has been evaluated with regard both to local and global mechanisms. Based on the obtained results, retrofitting operations have been hypothesized to allow for the new functionalization and the reuse of the building. In conclusion, the effectiveness of the consolidating interventions has been demonstrated by repeating the pushover analyses, whose results have enabled the complete seismic upgrading of the former tobacco industry.